Pemberdayaan Perpustakaan Desa melalui Implementasi Gerakan Nasional Gemar Membaca di Kecamatan Suwawa Kabupaten Bone Bolango - Malabar, Sayama; Salam, Salam; Lantowa, Jafar (Universitas Negeri Gorontalo, 2019)
The Village Project Program –Independent Campus aims to empower libraries by implementing the national reading movement. This program is implemented through education and training, mentoring, service, and guidance, which are expected to be sustainable through the awareness of related parties, especially the government and regional libraries. These parties are expected to pay attention to village library facilities and infrastructure that can realize the national reading movement program.Besides, to support the national reading movement, the program is also directed at forming literacy communities, literacy lodges, and reading parks in Bone Bolango.The Freedom to Learn - Independent Campus Community Service Program with the theme